Irisin Concentrations as a Myocardial Biomarker - Aydin, Suna; Aydin, Suleyman (Springer, 2016)
Mortality and morbidity from acute myocardial infarction (AMI), in which cardiomyocytes are damaged and destroyed, are increasing daily worldwide. Early intervention may decrease morbidity and potentially mortality in AMI. Currently troponins are seen as superior to all other biomarkers, but they have a major limitation since they do not become elevated during the initial hours of AMI. Therefore it is important to find a better biomarker for early diagnosis (within the initial hours). In this sense, a new thermogenic uncoupling protein, irisin, may be a useful marker to diagnose and make some prognosis regarding the long-term clinical outcome that might assist clinicians. Irisin is ubiquitously expressed in kidneys, liver, nerve sheath, skin, adipose tissue, and is abundantly synthesized in cardiac muscle. Serum and saliva concentrations also decrease with AMI. This chapter provides a brief description of AMI and current available tools for its diagosis, and some information about this candidate molecule irisin, including its concentration in human diseases. There is also an overview of isoproterenol (ISO)-induced myocardial infarction (MI) and irisin concentration in an animal model and how it changes in the serum and saliva of patients hospitalized after diagnosis of AMI. Finally, we discuss what should be known about the analysis of irisin in biological fluids. In summary, current data indicate that serum irisin measurement is probably a clinically effective test that offers some prognostic information to clinicians.
Keywords: Myocardial infarction; Irisin; Biomarker; Heart attack